Transformasi Ekonomi Lokal Melalui E-Commerce di Desa Parak Kepulauan Selayar - Badar, Muhammad; Nasir, Muhammad; N, Normiyati; Kasim, Andi Irwan; G, Muhammad Tahir; Tinri, Muh. Darwis Nur; Fitri, Riskal (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2025)
This community service aims to encourage local economic transformation in Parak Village, Selayar Islands through the use of e-commerce as a marketing medium for MSME products. The method of implementing the activity includes socialization, technical training for 8 sessions, and intensive assistance for 3 months to 50 MSME actors with a participatory approach and direct practice. The results of the activity showed a significant increase in the capacity of MSME actors in managing online stores independently, expanding market access to the regional level, and an increase in average revenue between 20% to 50%. Training and mentoring have proven to be effective in improving digital literacy and economic empowerment of village communities. However, challenges such as limited internet access and the need for advanced training still need to be addressed to ensure the sustainability of the digital economy transformation. In conclusion, e-commerce is a strategic solution to improve the competitiveness and economic welfare of the people of Parak Village, with recommendations to strengthen the digital ecosystem through cross-sector collaboration.